Quale formazione per la ricerca interdisciplinare? (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
This essay tries to answer the following questions. 1) What is interdisciplinary knowledge? 2) Is there a «method» of interdisciplinary research? 3) Are there any «skills» of interdisciplinary work? 4) How can the researcher who deals with artificial intelligence, robotics and biotechnology (and interdisciplinary research in general) learn to «govern» the ethical, legal and philosophical «implications» of his work? What is, gnoseologically, an «implication»? 5) What training is needed for these researchers? Is the problem solved by teaching a few hours of philosophy and a few hours of law in physics, computer science or biology courses? Or is there a need for a different and more effective approach?
Keywords: Interdisciplinary; methodology; research; skills; training